Minimization of The Diet Costs on The Three-Day Menu Example (Vallis Aurea, 2017)
Linear programming is a special field of applied mathematics that deals with solving optimization problems while certain conditions or constraints must be fulfilled. Aim of linear programming is to find a solution how to use or allocate a predetermined amount of resources with a predefined objective such as minimum cost, maximum revenue, maximum profit, etc. This paper presents the application of linear programming on the example of minimizing the diet costs. One of the basic human needs is the adequate daily intake of food in the body i.e. diet. In sufficient quantity food ensures the normal functioning of the human body, it gives energy for mental and physical work and raises the immune system. In this paper, the problem of diet is set to minimize the total cost of daily diet while the criteria for daily intake of a sufficient amount of all nutrients required for the normal functioning of the human body must be fulfilled.Carbohydrates, fats and proteins give energy to the human body. Carbohydrates are first consumed, then fat, and only in the cases of starvation body translates carbohydrates into energy. Daily energy needs depend on gender, age, body mass, body height and total daily physical activity. Furthermore, a three-day menus for a group of young and middle-aged people, between 19 and 50, separately for a group of men and women is provided.